Pengaruh Budaya Organisasi, Kepuasan Kerja, Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Hotel Di Kota Ambon - Leonora Ferdinandus (Jurnal Administrasi Terapan, 2024)
The hospitality industry is one of the most dynamic and competitive sectors, especially in growing cities like Ambon. This study aims to examine the influence of organizational culture, job satisfaction, and leadership style on hotel employee performance in Ambon City. A quantitative approach with a survey method was used in this research. This approach was chosen to measure the impact of independent variables (organizational culture, job satisfaction, and leadership style) on the dependent variable (employee performance) objectively through the collection and analysis of numerical data. The population in this study comprises all hotel employees in Ambon City. Purposive sampling was used to select the sample, with the criteria being employees who have worked at the hotel for at least one year and hold positions ranging from staff to manager. The sample size used was 125 employees from various hotels in Ambon City, selected proportionally from different types of hotels (3-star and 4-star) to ensure representativeness. Data collected through questionnaires were processed and analyzed using multiple regression analysis. Based on the results of the multiple regression analysis, it was found that the three independent variables significantly influence employee performance, both partially and simultaneously. The findings of this study are consistent with previous research, indicating the importance of organizational culture, job satisfaction, and leadership style in improving employee performance in the hospitality industry. Keywords: Organizational Culture, Job Satisfaction, Leadership Style, Employee Performance